Strategi Bersaing UMKM Kecantikan Berbasis Kearifan Lokal: Analisis SWOT pada Yakuzha Beauty and Health: [Competitive Strategy of Beauty MSMEs Based on Local Wisdom: A SWOT Analysis of Yakuzha Beauty and Health] - Sirajuddin Omsa; Nurhamsiani; Eka Astra Susilawaty (Milestone: Journal of Strategic Management, 2026)
In the background of global infrastructure construction and the transformation of the construction industry to an integrated service model, this study draws on strategic management theory, especially Porter's theory of competitive advantage and the resource-based view (RBV), to explore the research questions: 1. What are the strategic factors that contribute to the competitive advantage of CCC? 2. How are the strategic factors applied/implemented to contribute to the competitive advantage of CCC. And draw the competitive advantages of CCC to maintain its leading position in the highly competitive integrated building services field. This study is mainly based on interviews, through qualitative research and literature analysis, to explore the factors that CCC uses to build differentiated competitive advantages. The development of CCC in Indonesia shows that Chinese enterprises should pay attention to the comprehensive balance of technical capabilities, quality control, social responsibility and employee development in the process of "going out" to achieve a high-quality and responsible international development path. The researchers hope that this study can provide some reference for peer companies to enhance their competitive advantages, and at the same time provide strategic inspiration for international customers and other researchers to understand how Chinese integrated building service providers can gain competitive advantages in the evolving global infrastructure ecosystem. Abstrak Bahasa Indonesia: Dengan latar belakang konstruksi infrastruktur global dan transformasi industri konstruksi menjadi model layanan terintegrasi, penelitian ini mengacu pada teori manajemen strategis, terutama teori keunggulan kompetitif Porter dan pandangan berbasis sumber daya (RBV), untuk mengeksplorasi pertanyaan penelitian: 1. Apa saja faktor strategis yang berkontribusi pada keunggulan kompetitif CCC? 2. Bagaimana faktor strategis diterapkan/diimplementasikan untuk berkontribusi pada keunggulan kompetitif CCC. Dan menarik keunggulan kompetitif CCC untuk mempertahankan posisi terdepannya di bidang layanan bangunan terpadu yang sangat kompetitif. Penelitian ini terutama didasarkan pada wawancara, melalui penelitian kualitatif dan analisis literatur, untuk mengeksplorasi faktor-faktor yang digunakan CCC untuk membangun keunggulan kompetitif yang berbeda. Perkembangan CCC di Indonesia menunjukkan bahwa perusahaan Tiongkok harus memperhatikan keseimbangan komprehensif antara kemampuan teknis, kontrol kualitas, tanggung jawab sosial dan pengembangan karyawan dalam proses "keluar" untuk mencapai jalur pembangunan internasional yang berkualitas tinggi dan bertanggung jawab. Para peneliti berharap bahwa penelitian ini dapat memberikan beberapa referensi bagi perusahaan sejawat untuk meningkatkan keunggulan kompetitif mereka, dan pada saat yang sama memberikan inspirasi strategis bagi pelanggan internasional dan peneliti lain untuk memahami bagaimana penyedia layanan bangunan terintegrasi Tiongkok dapat memperoleh keunggulan kompetitif dalam ekosistem infrastruktur global yang berkembang.